Beliefs about Obedience Levels in Studies Conducted within the Milgram Paradigm: Better than Average Effect and Comparisons of Typical Behaviors by Residents of Various Nations - Grzyb, Tomasz; Dolinski, Dariusz (Frontiers in Psychology, 2017)
The article presents studies examining whether the better-than-average effect (BTA) appears in opinions regarding obedience of individuals participating in an experiment conducted in the Milgram paradigm. Participants are presented with a detailed description of the experiment, asked to declare at what moment an average participant would cease their participation in the study, and then asked to declare at what moment they themselves would quit the experiment. It turned out that the participants demonstrated a strong BTA effect. This effect also concerned those who had known the results of the Milgram experiment prior to the study. Interestingly, those individuals – in contrast to naive participants – judged that the average person would remain obedient for longer, but at the same time prior familiarity with the Milgram experiment did not impact convictions as to own obedience. By the same token, the BTA effect size was larger among those who had previously heard of the Milgram experiment than those who had not. Additionally, study participants were asked to estimate the behaviour of the average resident of their country (Poland), as well as of average residents of several other European countries. It turned out that in participants’ judgement the average Pole would withdraw from the experiment quicker than the average Russian and average German, but later than average residents of France and England.